6 - Means Testing: The Dilemma of Targeting Subsidies in African Higher Education: Abebayehu A. Tekleselassie & D. Bruce Johnstone - D. Bruce Johnstone (Journal of Higher Education in Africa, 2004)
Means testing, a form of subsidy targeting, attempts to distribute at least some higher education subsidies on the basis of need or estimated ability to pay. This article explores the major principles, approaches, and challenges as well as some of the controversies surrounding means testing, taking into account the unique context of the African continent. For example, in many African countries incomes are not only low but are also frequently hidden or partly in kind. Assets are often both minimal and extremely illiquid. These conditions limit possible cash contri- butions toward higher education but also make it difficult to measure and to verify the subsidies to which many families are entitled. Therefore, many developing countries complement measures or estimates of income and assets with so-called categorical indicators of need (e.g., race/tribe/ethnicity, parents’ education, type of employment, secondary school attendance, possession of an automobile or access to a car driver) which are readily observable and more difficult to hide than con- ventional measures of incomes or assets. This article acknowledges some imper- fection in these measures but argues that rough justice in estimating ability to pay is still preferable to equal subsidies for all. It concludes with some recommenda- tions about targeting subsidies to higher education in Africa.